Does neighbourhood walkability moderate the effects of mass media communication strategies to promote regular physical activity? - Barnes, R.; Giles-Corti, B.; Bauman, A.; Rosenberg, M.; Bull, F.C.; Leavy, Justine (Springer New York LLC, 2013)
Background: Mass media campaigns are widely used in Australia and elsewhere to promote physical activity among adults. Neighbourhood walkability is consistently shown to be associated with walking and total activity. Campaigns may have different effects on individuals living in high and low walkable neighbourhoods. Purpose: The purpose of this study is to compare pre- and post-campaign cognitive and behavioural impacts of the Heart Foundation’s Find Thirty every day® campaign, in respondents living in high and lower walkable neighbourhoods. Methods: Pre- and post-campaign cross-sectional survey data were linked with objectively measured neighbourhood walkability. Cognitive and behavioural impacts were assessed using logistic regression stratified by walkability. Results: Cognitive impacts were significantly higher post-campaign and consistently higher in respondents in high compared with lower walkable neighbourhoods. Post campaign sufficient activity was significantly higher and transport walking significantly lower, but only in residents of lower walkable areas. Conclusions: Cognitive impacts of mass media physical activity campaigns may be enhanced by living in a more walkable neighbourhood.